Estudio de pre-factibilidad para la implementación de una planta productora de bebida energética a base de maca (lepidium meyenii) endulzado con stevia - Infantas Montaldo, Errol Eduardo (2019)
The following pre-feasibility study will analyze the commercial, technical, economic and financial viability of the implementation of a factory producing an energy drink based on maca sweetened with Stevia in Peru.